PENGELOLAAN AKTIVA DAN KEWAJIBAN DALAM PERBANKAN SYARIAH - Imaduddin, Muhammad (Al-Infaq: Jurnal Ekonomi Islam, 2010)
This paper aims to describe the Asset and Liability Management concept in an Islamic Bank. It employs descriptive analysis and shall utilize the concept to emphasize on intermediary function. The study explores several basic definitions in the application of aforesaid concept. It covers current challenges and recommendation of several issues regarding the Asset and Liabilibity Management. It is expected to view on practical prespective in an Islamic bank.